Optimasi Gizi Pada Bahan Makanan Balita Menggunakan Algoritme Genetika - Vivilia Putri Agustin; Imam Cholissodin; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In the Golden Age (children under five years old) have an important phase in child growth. Based on Basic Health Research in 2013, the development of children in East Java is still experiencing nutritional problems. The first because, lack of knowledge of parents to the nutritional needs of children. The second because, the lack of attention to the price of food in accordance with food ingredients that have balanced nutrition.One efforts of Dinkes Malang was involving Posyandu to do counseling related to improve child nutrition. However, these efforts were still experiencing obstacles in the form of the number of portions of food given to each children has not been adjusted based on weight and age, in addition the children lack variety of foodstuffs. Thus, the reseracher search a system to optimize it. Genetic algorithm was a Algorithm that was often used to overcome the problem of optimization. The results of the system in the form of lists of food and weight and price adjusted to the weight and age of children.Based on the test results obtained optimal parameters that the optimal population amount of 100, the optimal generation amount of 70 and the optimal combination of cr value and mr value was 0.5 and 0.5 resulted in a fitness value of 50.821.